Nalar Arab dalam Masyarakat Indonesia: Dulu, Kini dan Esok - Ibnu Hamad (Antropologi Indonesia, 2005)
The author argues that the Arab mind entered Indonesian society since the onset of Islam spreading in the 7th century. The development of the Arab mind has its own dynamic and inseparable from Islamic thought. The touch with Hindu-Budha cultural values created Kejawen among the Javanese; the contact with Dutch colonialism resulted acceptance of school system which brings secularism to Indonesian society. In the 80's, the Arab mind was suppressed by politically supported western mind through various ways. Globalization brings another challenge to the Arab mind that, interestingly, strengthens of Islamic identity among younger generation. Key words: The Arab mind; Javanese Islamic thought; political factor; Indonesia.